Association Analyses of TP53 Mutation With Prognosis, Tumor Mutational Burden, and Immunological Features in Acute Myeloid Leukemia - Wen, Xiang-mei; Xu, Zi-jun; Jin, Ye; Xia, Pei-hui; Ma, Ji-chun; Qian, Wei; Lin, Jiang; Qian, Jun (Frontiers in Immunology, 2021)
Acute myeloid leukemia (AML) is a heterogeneous disease related to a broad spectrum of molecular alterations. The successes of immunotherapies treating solid tumors and a deeper understanding of the immune systems of patients with hematologic malignancies have promoted to develop immunotherapies for the treatment of AML. And high tumor mutational burden (TMB) is an emerging predictive biomarker for response to immunotherapy. However, the association of gene mutation in AML with TMB and immunological features remains unknown. In our study, based on The Cancer Genome Atlas (TCGA) and BeatAML cohorts, 20 frequently mutated genes were found to be covered by both two datasets in AML. And TP53 mutation was associated with a poor prognosis and its mutation displayed exclusive with other common mutated genes in both two datasets. Moreover, TP53 mutation correlated with TMB and the immune microenvironment. Gene set enrichment analysis (GSEA) showed TP53 mutation upregulated signaling pathways involved in the immune system. In summary, TP53 mutation is frequently mutated in AML, and its mutation is associated with dismal outcome, TMB and immunological features, which may serve as a biomarker to predict immune response in AML.